2002
DOI: 10.1002/jbm.10086
|View full text |Cite
|
Sign up to set email alerts
|

Collagen and bone viscoelasticity: A dynamic mechanical analysis

Abstract: The purpose of this study was to explore the effects of changes in Type I collagen on the viscoelasticity of bone. Bone coupons were heated at either 100 or 200 degrees C to induce the thermal denaturation of Type I collagen. Half of these specimens were rehydrated after heat treatment; the other half were tested in a dry condition. The degree of denatured collagen (DC%) was analyzed by a selective digestion technique with the use of alpha-chymotrypsin. Isothermal (37 degrees C) and variable temperature tests … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(79 citation statements)
references
References 35 publications
(43 reference statements)
5
64
0
1
Order By: Relevance
“…So staying with our bone example, if bone behaviour in physiological conditions is linear elastic, then, in the range of deformation rates that is physiologically possible, bones should exhibit no significant viscous dissipation, which can be verified with isothermal experiments [39].…”
Section: (A) Deductive Modelssupporting
confidence: 55%
“…So staying with our bone example, if bone behaviour in physiological conditions is linear elastic, then, in the range of deformation rates that is physiologically possible, bones should exhibit no significant viscous dissipation, which can be verified with isothermal experiments [39].…”
Section: (A) Deductive Modelssupporting
confidence: 55%
“…It is accepted that the mineral phase is the main contributor to the elastic and strength and Agrawal, 1996). Also, dehydration affects the viscoelastic behaviour of cortical bone: for instance, it reduces the loss factor without appreciable changes in the storage modulus (Yamashita et al, 2002), and increases the relaxation rate (Sasaki and Enyo, 1995). Because in vivo bone fractures are often initiated and/or promoted by cracks, Fracture Mechanics emerges as an essential tool to assess bone tissue quality, in order to improve the diagnoses of fracture risks and the treatment of bone diseases (Wang and Puram, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of collagen in compact bone definitely contributes to this behavior as it was shown that biological materials lose their viscoelastic characteristics with a decrease in collagen content [33]. In addition, a dynamic mechanical analysis experiment on compact bone revealed that water plays a significant role as well [31]. Another series of research articles came to the conclusion that fluid in the vascular channels of compact bone does not significantly contribute to viscoelasticity but the interaction between the fluid and calcified matrix does [34].…”
Section: Time Dependent Properties: Viscoelasticitymentioning
confidence: 99%